Relação entre área de loja e desempenho de venda em contexto de multicanalidade - Razuk Filho, Horacio (2018)
This thesis is based in the multichannel retail environment, which is a recurrent theme especially after the rapid growth in e-commerce sales in recent past (12% in 2017 over 2016 in Brazil) that has contributed to the entrance of major traditional retailers in the electronic channel. In spite of that, there has been very little discussion on using these online tools to reduce store space and make it more efficient. Because even though there is some competition between the physical and digital channels in sales and distribution, evidences point that they are complementary with the store serving as showroom to the e-commerce sales in the region. The main objective of this research is to investigate the relationship between physical store size and sales both off-line and online within the region of influence of the store. To achieve this goal, a field experiment was conducted with data from four stores of a retail chain in the city of São Paulo, two of which had their sales area reduced. The results indicate that after the reduction, sales from both stores were impacted, but in the store where this reduction was made in conjunction with other changes in visual merchandising the impact was positive, while in the store where the reductions was simpler this impact was negative. In regards to the online sales, there was no measurable change in sales trend. The implications of this research include insights to managers of this sector about investments and expansion plans within this context.